Low frequency of IL-10+ B cells in patients with atherosclerosis is related with inflammatory condition (2020)
ABSTRACT:Background and aims: B cells involvement in animal models of atherosclerosis has been unequivocally established. However, the role of these cells in patients with atherosclerosis is almost unknown. Besides the production of antibodies, B cells can also exhibit regulatory functions mainly through IL-10. Here, we characterized human B cell subsets, their production of IL-10 in patients with atherosclerosis and their potential association with inflammation. Methods: Patients with confirmed atherosclerotic events and controls with low cardiovascular risk were included. B cells subsets were determined in mononuclear cells (PBMC) using flow cytometry. PBMC were cultured ex vivo (5 h) and in vitro (48 h) to determine IL-10+ B cells and in some cases TNF-α+ and IFN-γ+ CD4+ T cells. The inflammatory state of the participants was determined through high sensitivity C reactive protein levels. Results: Increase in percentage and number of plasmablasts was observed in patients with atherosclerosis compared with controls. A decreased frequency of IL-10+ B cells was observed in patients, both in ex vivo and in vitro cultures. This decrease was detected in transitional, memory, and plasmablast subsets. Interestingly, the reduction of IL-10+ B cells negatively and significantly correlated with the inflammatory condition of the studied subjects and associated with an increased frequency of TNF-α+ and IFN-γ+ CD4+ T cells. The blockade of IL-10R did not show further effect in T cells activation. Conclusions: There is an association between the inflammatory state and a reduction of IL-10+ B cells that could contribute to the development of atherosclerosis.